Adsorption-Desorption Characteristics of Polychlorinated Biphenyls on Various Polymers Commonly Found in Laboratories - Cseh, Tibor (1989)
Adsorption and desorption of Aroclor 1254 (a mixture of polychlorinated biphenyls [PCBs]) from 0.25% (wt/vol) aqueous solutions of Triton X-100 on polymeric materials common in laboratories (red vacuum rubber, latex, Tygon, Norprene, manosil, polyethylene, polypropylene, phenoxy resin, nylon, and Teflon) is described. Teflon, nylon, and phenoxy resins showed the lowest adsorptions, with efficiencies of 3.4, 22.9, and 33.0%, respectively. The other polymers adsorbed more than 90% of Aroclor 1254 under similar conditions. Adsorption of PCBs was found to increase with the lipophilicity of the polymer and to be irreversible on soft polymers. The variation in the adsorption efficiencies of these polymers toward PCBs is apparently related to variations in the chemical composition, electronic properties, and degree of softness of these polymers. The present study showed that Teflon, with less than 4% adsorption and more than 99% desorption of Aroclor 1254, is the best candidate for use in biological laboratory work.